THE EFFECT OF TURMERIC AND DRAGON FRUIT PEEL IN DRINKING WATER ON BROILER PERFORMANCE - S., Yulaika; Dewi, G. A. M. K.; Puspani, E. (Jurnal Peternakan Tropika; Vol 12 No 2 (2024): Vol. 12 No. 2 Tahun 2024; March - April, 2024)
This study aims to determine the effect of turmeric and dragon fruit peel extract in drinking water on broiler performance that have been carried out for 28 days with homogeneous body weights ranging from 39,8g ± 2,73. The study used a Completely Randomized Design (CRD) consisting of four treatments, four replications, with five broilers in each unit. The four treatments were P0 (drinking water without extract as control), P1 (drinking water+4% turmeric extract), P2 (drinking water+4% dragon fruit peel extract), and P3 (drinking water+4% a mixture of turmeric and dragon fruit peel extract). The variables observed were ration consumption, drinking water consumption, final weight, broiler body weight gain and ration conversion. The results showed that ration consumption, final weight, broiler body weight gain and ration conversion was not show significantly increase (P>0,05) in all treatments. But the provision of treatment P1 and P2 can significantly (P<0,05) increase broiler drinking water consumption compared to treatment P0. The conclusion of this study is the provision of turmeric extract, dragon fruit peel extract and a mixture of both with a concentration of 4% though drinking water have been unable to affect the final weight, body weight gain, ration consumption and broiler ration conversion, but can affect broiler drinking water consumption.